The protection of civil rights for the Shi’ite refugees of Sampang, East Java: a systemic governance approach to restore the refugees’ Rights - Dani Muhtada; Suhadi Suhadi; In’am Zaidi; Rayyan Alkhair (IAIN Salatiga, 2022)
Hundreds of victims of the 2012 Sunni-Shia conflict in Sampang are still living in refugee camps in Sidoarjo, East Java. They still keep the dream to return back to their home village in Sampang. Even though the majority of them have pledged to return to Sunnis in early November 2020, no one could guarantee that they can definitely return to their home village after the pledge. This article seeks to identify the factors that make it difficult for the Sampang Shia refugees to obtain their civil rights as well as to formulate strategic policies to restore these rights. This article indicates that the Shia refugees, who live in the refugee camp, have already got some of their civil rights back, including the rights to access health facilities, education and administration services. However, there are two fundamental civil rights that have not been fulfilled, namely the freedom of religion and the right to live back in their home village. It argues that two main factors prevent them from returning to their home village: strong resistance from the community and the weak role of the state. The article suggests that the government needs to employ a systemic governance approach to fully restore the civil rights of the Sampang Shia refugees.